Defective lipid droplet biogenesis exacerbates oleic acid-induced cellular homeostasis disruption and ferroptosis in mouse cardiac endothelial cells - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Zhengchao Wang; Kiana Roudbari; Jenny Z. Hu; Mi Wang; Pin-Lan Li; Yang Zhang; Xiang Li (Cell Death Discovery)
Abstract Endothelial dysfunction is a hallmark of various metabolic disorders and plays a pivotal role in the progression of cardiovascular diseases, including coronary microvascular dysfunction and myocardial ischemia. Lipid droplets (LDs) have emerged as key regulators of fatty acid metabolism in endothelial cells (ECs), but their functional role in lipotoxicity-induced EC damage in the context of coronary microvascular dysfunction remains unclear. Here, we examined the contribution of LD biogenesis to oleic acid-induced lipotoxic effects in mouse cardiac ECs (MCECs). Our findings reveal that oleic acid markedly increases LD biogenesis in MCECs via a diacylglycerol O-acyltransferase 1 (DGAT1)-dependent pathway. This process is accompanied by substantial disruptions in cellular homeostasis, including elevated endoplasmic reticulum (ER) stress, impaired mitochondrial respiration, reduced ATP production, and heightened hypoxic responses. Furthermore, oleic acid-induced lipotoxicity is primarily mediated by ferroptosis−a form of lipid peroxide-dependent, caspase-independent cell death. Notably, pharmacological inhibition or genetic knockdown of DGAT1, which diminishes LD biogenesis, exacerbates oleic acid-induced cellular stress, mitochondrial dysfunction, and ferroptosis in MCECs. These results suggest that LD biogenesis plays a protective role in mitigating lipotoxicity, preserving mitochondrial function, and preventing lipid peroxide accumulation and ferroptosis, thereby safeguarding cardiac microvascular endothelial function in the context of metabolic disorders.